Scenarios of Land Use and Land Cover Change and Their Multiple Impacts on Natural Capital in Tanzania. (18th September 2018) - Capitani, Claudia; van Soesbergen, Arnout; Mukama, Kusaga; Malugu, Isaac; Mbilinyi, Boniface; Chamuya, Nurdin; Kempen, Bas; Malimbwi, Rogers; Mant, Rebecca; Munishi, Panteleo; Njana, Marco Andrew; Ortmann, Antonia; et al.
Summary: Reducing emissions from deforestation and forest degradation plus the conservation of forest carbon stocks, sustainable management of forests and enhancement of forest carbon stocks in developing countries (REDD+) requires information on land-use and land-cover changes (LULCCs) and carbon emission trends from the past to the present and into the future. Here, we use the results of participatory scenario development in Tanzania to assess the potential interacting impacts on carbon stock, biodiversity and water yield of alternative scenarios where REDD+ is or is not effectively implemented by 2025, a green economy (GE) scenario and a business as usual (BAU) scenario, respectively. Under the BAU scenario, LULCCs will cause 296 million tonnes of carbon (MtC) national stock loss by 2025, reduce the extent of suitable habitats for endemic and rare species (mainly in encroached protected mountain forests) and change water yields. In the GE scenario, national stock loss decreases to 133 MtC. In this scenario, consistent LULCC impacts occur within small forest patches with high carbon density, water catchment capacity and biodiversity richness. Opportunities for maximizing carbon emission reductions nationally are largely related to sustainable woodland management, but also contain trade-offs with biodiversity conservation and changes in water availability.